2015
DOI: 10.48550/arxiv.1504.00476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Some aspects of symmetric Gamma process mixtures

Abstract: In this article, we present some specific aspects of symmetric Gamma process mixtures for use in regression models. We propose a new Gibbs sampler for simulating the posterior and we establish adaptive posterior rates of convergence related to the Gaussian mean regression problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Simulation results. We use the algorithm of Naulet and Barat (2015) for simulating samples from posterior distributions of Gamma process mixtures. The base measure α on R 2 × [0, 2π] of the mixing Gamma process is taken as the independent product of a normal distribution on R 2 with covariance matrix diag(1/2, 1/2) and the uniform distribution on [0, 2π].…”
Section: Simulations Examplesmentioning
confidence: 99%
“…Simulation results. We use the algorithm of Naulet and Barat (2015) for simulating samples from posterior distributions of Gamma process mixtures. The base measure α on R 2 × [0, 2π] of the mixing Gamma process is taken as the independent product of a normal distribution on R 2 with covariance matrix diag(1/2, 1/2) and the uniform distribution on [0, 2π].…”
Section: Simulations Examplesmentioning
confidence: 99%
“…Notice that equation ( 5) forbids the use of the classical inverse-Gamma distribution as prior distribution on σ because of its heavy tail. In fact, it is always possible to weaken equation ( 5) to allow for Inverse-Gamma distribution (see Canale and De Blasi (2013); Naulet and Barat (2015)) but it complicates the proofs with no contribution to the subject of the paper. We found that among the usual distributions the inverse-Gaussian is more suitable for our purpose since it fulfills all the equations (5) to (7), as shown in proposition 1.…”
Section: Family Of Priorsmentioning
confidence: 99%
“…Nonparametric mixture models are highly popular in the Bayesian nonparametric literature, due to both their reknown flexibility and relative easiness of implementation, see Hjort et al (2010) for a review. They have been used in particular for density estimation, clustering and classification and recently nonparametric mixture models have also been proposed in nonlinear regression models, see for instance de Jonge and van Zanten (2010); Wolpert et al (2011); Naulet and Barat (2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations